P66 A peer led partnership achieves whole substance misuse service HCV testing and treatment. (28th September 2020) - RIchardson, Carrie; Burns, Mark; Morris, Danny; Dilks, Breanne; Ryder, Stephen; Willoughby, Anna
Abstract : Background: People who inject drugs (PWID) living in remote settings across the UK commonly experience levels of isolation with increased difficulty accessing hepatitis C (HCV) testing and treatment. Many individuals may be engaged with substance misuse services (SMS) while experiencing difficulties in navigating pathways and overcoming barriers to accessing secondary care resulting in missed opportunities for HCV treatment. Objective: To determine if the introduction of peer support, working collaboratively with clinicians and SMS providers by providing peer-led pro-active engagement, support and education can promote treatment uptake and reduce testing to treatment pathway times to 4 weeks or less. Description of intervention: A Peer Support Lead supported by peers with lived experience of HCV, working in partnership with a Clinical Nurse Specialist (CNS) and SMS practitioners coordinated a two-week intensive HCV PCR testing programme targeting service users at a small rural town SMS. An information sharing agreement between services was established, facilitating timelier liaison and responsive peer support. Testing was coordinated alongside routine appointments to ensure delivery to all PWID with the service and aimed to test 121 patients identified as at risk. All those identified as HCV +ve were supported by peers to access treatment, delivered within the SMS community. Effectiveness: The model was welcomed by service users who valued reassurance and guidance in getting tested and treated. Of the 18 patients referred, to date 15 have started treatment. Results from the 121 service-users who were identified as at risk were highly productive. 116 individuals were tested and results demonstrated 35 as antibody + for HCV, 18 PCR + and 15 commenced treatment at the time of writing. Additionally, SMS Recovery Coordinators demonstrated increased confidence in promoting HCV testing and treatment. Conclusion and Next Steps: Objectives were met - in shortening the test to treatment pathway and 83% of service-users identified as HCV + commencing treatment. The successful peer led multi-agency approach has proved replicable and is now being expanded across other locations. The project also has proven effective in promoting a visible message of simplicity and ease of HCV treatment to service-users. Disclosure of Interest Statement: The Hepatitis C Trust has received funding via the NHS England elimination agenda through Merck Sharp & Dohme to fund the role of Peer Support Lead.